Positive electrode photocatalytic material for solid-state battery, preparation method of positive electrode photocatalytic material, battery positive electrode and solid-state battery
By introducing multi-element alloy nanoparticles and vacancy/defect-rich semiconductor nanoarray structures into the cathode catalyst of solid-state batteries, the energy loss problem of solid-state metal-gas batteries at low temperatures was solved, achieving efficient photo-thermal-electric synergistic conversion and charge transport, thus improving the energy utilization efficiency of the battery.
Patent Information
- Application Number
- CN202511327464.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2026-02-03
AI Technical Summary
Existing solid-state metal-gas batteries are difficult to work effectively at low temperatures. The kinetics of gas reduction and precipitation reactions are slow, resulting in high energy loss and low energy utilization efficiency. Furthermore, semiconductor catalysts are difficult to effectively utilize visible light in the solar spectrum.
A cathode catalyst with a composite structure of multi-element alloy nanoparticles and a one-dimensional semiconductor nanoarray rich in vacancies/defects was designed. Through strong interactions, it achieves broad-spectrum strong absorption and efficient photo-thermal-electric synergistic conversion, thereby improving battery performance under low-temperature conditions.
At low temperatures, the photocatalytic and electrochemical performance was significantly improved, the photocurrent density and photo-thermal-electric conversion efficiency were increased, the charge transport impedance was reduced, and efficient energy utilization was achieved.
Smart Images

Figure CN121446473A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage battery technology, and relates to a multi-field coupled cathode material for low-temperature solid-state batteries and its preparation method. More specifically, it relates to a photo-thermal-electric conversion metal / semiconductor nanocomposite structure cathode catalyst material for light-driven solid-state batteries that operates in low-temperature environments, its preparation method, battery cathode, and solid-state battery. Background Technology
[0002] Solid-state energy storage / power batteries, which use inorganic solid-state electrolytes to replace traditional organic liquid electrolytes, have become a trend in energy storage / power battery development due to their advantages in safety and high specific energy. Among them, solid-state metal-gas batteries, including metal-air batteries and metal-carbon dioxide batteries, have become a current research hotspot due to their significant advantages in energy density and environmental friendliness. However, the research progress of metal-air batteries has been exceptionally slow, and their application is severely limited. The main reason is that the extremely slow kinetics of the gas (O2 / CO2) reduction and precipitation reactions during discharge / charge mean that the battery system often needs to operate at a high charging plateau potential and a low discharging plateau potential, resulting in huge energy loss, very low energy utilization efficiency, and difficulty in achieving reversible cycling. In addition, the low ion transport in solid electrolytes, electrolyte interfaces, and electrode materials makes it difficult for solid-state batteries, especially solid-state metal-gas batteries, to operate effectively below zero degrees Celsius, thus limiting the application of all-solid-state batteries.
[0003] Solar energy is the most abundant energy source available to humankind. Currently, the main methods for developing and utilizing solar energy include photothermal conversion, photoelectric conversion, and photochemical conversion. Solar photothermal / photoelectric conversion is the most common, direct, and effective way to utilize solar energy. Based on their previous research in solar photothermal conversion and their accumulated experience in all-solid-state lithium-ion batteries, the inventors, in collaboration with partners, proposed the Solar Photothermal Battery (SPTB) technology. Through the strong metallic plasmon photothermal effect of ruthenium nanoparticles, they achieved stable cycling of an all-solid-state lithium-air battery at -73℃, and further developed ultra-low temperature all-solid-state lithium-air batteries and ultra-wide temperature all-solid-state lithium metal batteries.
[0004] By introducing sunlight into metal-air batteries using semiconductor materials, and utilizing their conduction and valence band energy levels to achieve the energy conversion of "light energy → electrical energy (electron-hole)," the kinetic reaction of the positive electrode during charging / discharging can be effectively promoted, thus improving the energy utilization efficiency of the battery. For example, Professor Xu Jijing's team at Jilin University used rutile titanium dioxide (TiO2) nanorod arrays grown on carbon cloth as photocatalysts. By transferring photogenerated electrons from the TiO2 conduction band to the molecular orbitals of carbon dioxide gas, they increased the discharge plateau potential of the prepared organic Li-CO2 battery from 2.69V to 2.82V. Professor Peng Huisheng's team at Fudan University prepared carbon nanotube / carbon nitride (CNT / C3N4) composite photocatalytic positive electrode materials to efficiently absorb light energy, thereby reducing the chemical reaction barrier of the battery and accelerating the formation and decomposition of discharge products. This increased the discharge plateau potential of the organic lithium carbon dioxide battery to 3.24V, achieving an energy conversion efficiency of 98.8%.
[0005] However, to provide sufficient energy to meet the thermodynamic conditions for the discharge / charge reaction, most currently disclosed semiconductor catalysts are broad optical bandgap materials with high conduction band and deep valence band energy levels, making it difficult to utilize the most energy-concentrated visible light in the solar spectrum. Semiconductor-metal composite structures can achieve broadband strong absorption of sunlight and efficient photoelectric / thermal synergistic conversion to a certain extent; however, no research has been reported on further improving the discharge / charge reaction kinetics and battery cycle performance of solid-state metal-gas batteries through the design of catalytically active sites on the surface of metal-semiconductor composite structures and the regulation of metal-semiconductor interface interactions.
[0006] Therefore, for this technical field, it is particularly important to design and create a composite cathode catalyst material consisting of multi-element alloy nanoparticles and low-dimensional semiconductor nanoarray structures that has abundant catalytic active sites, can absorb sunlight with a wide spectrum and high efficiency, and achieve efficient photo-thermal-electric synergistic conversion. Summary of the Invention
[0007] Based on the aforementioned status quo of existing technologies, this invention provides a broadband, high-absorption, and high-efficiency photo-thermal-electric conversion nanocomposite cathode photocatalytic material for light-driven solid-state batteries operating at low temperatures, along with its preparation method, battery cathode, and solid-state battery. The catalytic material of this invention is created by combining multi-element alloy nanoparticles with a one-dimensional oxide semiconductor nanoarray structure rich in vacancies / defects, forming a metal-semiconductor nanocomposite structure with excellent photocatalytic performance and energy conversion efficiency. This provides a novel material solution for the efficient operation of light-driven solid-state batteries under low-temperature conditions.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A photocatalyst material for solid-state batteries comprises a one-dimensional semiconductor nanoarray composite structure containing vacancies / defects and multi-element alloy nanoparticles, wherein:
[0010] A one-dimensional semiconductor nanoarray composite structure containing vacancies / defects, wherein the one-dimensional semiconductor nanoarray composite structure includes an oxide semiconductor nanoarray structure containing oxygen vacancies / defects or a sulfide semiconductor nanoarray structure containing sulfur vacancies / defects.
[0011] Multi-element alloy nanoparticles, wherein the multi-element alloy nanoparticles are binary alloy particles and / or ternary or higher entropy alloy particles with sizes in the sub-nanometer and nanoscale range.
[0012] The multi-element alloy nanoparticles are assembled on the one-dimensional semiconductor nanoarray composite structure through strong interactions, together forming a metal-semiconductor nanocomposite cathode catalyst structure with broad-spectrum strong absorption and efficient photo-thermal-electric synergistic conversion.
[0013] Preferably, oxide semiconductor nanoarray structures containing oxygen vacancies / defects include, but are not limited to, Ti5O9 nanoarray structures containing oxygen vacancies, TiO2 nanoarrays containing oxygen vacancies, or TiO2 nanoarrays that introduce additional oxygen vacancies by doping with manganese (Mn) or chromium (Cr). x Nanoarrays.
[0014] As a preferred embodiment, the sulfide semiconductor nanoarray structure containing sulfur vacancies / defects includes, but is not limited to, MoS2 nanoarrays containing sulfur vacancies, WS2 nanoarrays generated under transition metal doping conditions (such as cobalt, nickel or iron); or ZnS nanoarrays prepared by chemical vapor deposition (CVD) under high-temperature sulfidation conditions, which have a high density of sulfur vacancies.
[0015] As a preferred option, the multi-element alloy nanoparticles include, but are not limited to, binary alloys and high-entropy alloy particles with ternary or higher elements formed by metals such as Ru, Ir, Co, Ni, Fe, Cu, Zn, and Mo, with sizes ranging from sub-nanometer to nanometer scale.
[0016] This invention also discloses a method for preparing the above-mentioned positive photocatalytic material, the specific steps of which are as follows:
[0017] Step 1: Substrate preparation
[0018] Nanoarray structures are prepared from oxide or sulfide semiconductor materials with standard stoichiometry (such as TiO2) using traditional physicochemical methods such as hydrothermal methods.
[0019] Step 2: Catalyst introduction
[0020] The obtained nanoarray structure was immersed in a multi-metal salt solution (such as gold chloride solution and ruthenium chloride solution) to uniformly deposit metal ions.
[0021] Step 3: Structure Synthesis
[0022] The immersed material is subjected to instantaneous high-temperature heat treatment using the Joule heating method (temperature range from 500℃ to 1200℃, treatment time from several seconds to several minutes) to form multi-element alloy nanoparticles and one-dimensional semiconductor nanoarray structures rich in vacancies / defects, and a strong interaction is established between the two.
[0023] This invention further enhances the photocatalytic performance and reversible charge transport and storage performance at low temperatures of the material by introducing catalytically active sites such as oxygen vacancies, sulfur vacancies, and defects.
[0024] The key features of this invention are as follows:
[0025] 1) Broad-spectrum strong absorption performance
[0026] This invention achieves broad-spectrum strong absorption of sunlight by coupling the plasmon effect of multi-element alloy nanoparticles with the photocatalytic properties of one-dimensional semiconductor nanoarrays.
[0027] 2) High-efficiency light-heat-electricity synergistic conversion
[0028] The strong interaction between the multi-element alloy nanoparticles and the semiconductor nanoarray rich in vacancies / defects significantly improves the separation efficiency of photogenerated charges, thereby enhancing the synergistic conversion capability of light-heat-electric energy.
[0029] 3) Low-temperature performance optimization
[0030] This invention further enhances the reversible charge transport and storage performance of materials under low-temperature conditions by introducing catalytically active sites such as oxygen vacancies, sulfur vacancies, and defects. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the preparation process of the positive photocatalytic material in an embodiment of the present invention.
[0032] Figure 2 This is a SEM characterization image of the TiO2 semiconductor nanoarray structure in an embodiment of the present invention.
[0033] Figure 3 This is a SEM image of the TiO2 nanostructure after soaking and Joule heat treatment in an embodiment of the present invention.
[0034] Figure 4 The image shows the XRD pattern of the TiO2 nanostructures prepared by the method of this embodiment of the invention after soaking and Joule heat treatment.
[0035] Figure 5 The images show the TEM image and optical absorption spectrum of the AuRu-Ti5O9 metal-semiconductor nanocomposite structure in this embodiment of the invention.
[0036] Figure 6 This is a schematic diagram of the structure of a metal-semiconductor nanocomposite cathode catalyst. Detailed Implementation
[0037] The preferred embodiments of the present invention will be described in detail below.
[0038] like Figure 6 As shown, the positive electrode photocatalyst material in this embodiment includes a one-dimensional semiconductor nanoarray composite structure rich in vacancies / defects and multi-element alloy nanoparticles: the semiconductor nanoarray structure rich in oxygen vacancies / defects includes, but is not limited to, a Ti5O9 nanoarray structure rich in oxygen vacancies, a TiO2 nanoarray rich in oxygen vacancies, or a TiO2 nanoarray with additional oxygen vacancies introduced by doping with manganese (Mn) or chromium (Cr). x Nanoarrays and sulfide semiconductor nanoarray structures rich in sulfur vacancies / defects include, but are not limited to, MoS2 nanoarrays rich in sulfur vacancies, WS2 nanoarrays generated under transition metal doping conditions (such as cobalt, nickel or iron); or ZnS nanoarrays prepared by chemical vapor deposition (CVD) under high-temperature sulfidation conditions, which have high density of sulfur vacancies.
[0039] Multi-element alloy nanoparticles: including but not limited to binary alloys and high-entropy alloy particles with ternary or higher elements formed by metals such as Ru, Ir, Co, Ni, Fe, Cu, Zn, and Mo, with sizes ranging from sub-nanometer to nanometer scale.
[0040] Multi-element alloy nanoparticles are assembled on a one-dimensional semiconductor nanoarray structure rich in vacancies / defects through strong interactions, forming a metal-semiconductor nanocomposite cathode catalyst structure with broad-spectrum strong absorption and efficient photo-thermal-electric synergistic conversion performance.
[0041] Example 1:
[0042] like Figure 1 As shown in this embodiment, a method for preparing a one-dimensional oxide semiconductor nanoarray rich in oxygen vacancies and a composite structure of multi-element alloy nanoparticles (i.e., a positive electrode photocatalytic material) is described below:
[0043] Substrate preparation
[0044] A hydrothermal method was used to prepare an oxide semiconductor nanoarray structure with standard stoichiometry. Specifically, a titanium substrate (TiO2) was placed in a mixed solution containing tetrabutyl titanate, acetic acid, and deionized water, and a hydrothermal reaction was carried out at 200°C for 12 hours to form a uniform TiO2 nanoarray.
[0045] Catalyst introduction
[0046] The obtained TiO2 nanoarray was immersed in a mixed solution of 0.1M gold chloride (HAuCl4) and ruthenium chloride (RuCl3) for 2 hours to allow metal ions to be uniformly adsorbed on the TiO2 surface.
[0047] Structural synthesis
[0048] The immersed samples were subjected to Joule heating instantaneous high-temperature treatment at 800°C for 30 seconds. This step formed RuAu bimetallic nanoparticles on the surface of the TiO2 nanoarray, while simultaneously introducing oxygen vacancies, resulting in a metal-semiconductor composite nanoarray structure.
[0049] Material characterization
[0050] The morphology of the sample was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), confirming the formation of uniformly distributed RuAu bimetallic nanoparticles and an oxygen-vacancy-containing TiO2 nanoarray. X-ray photoelectron spectroscopy (XPS) analysis showed a significant increase in the oxygen vacancy content on the sample surface.
[0051] Example 2:
[0052] A method for preparing a composite structure of a one-dimensional sulfide semiconductor nanoarray rich in sulfur vacancies and high-entropy alloy particles (i.e., a positive electrode photocatalytic material) includes the following specific steps:
[0053] Substrate preparation
[0054] Molybdenum sulfide (MoS2) in standard stoichiometric ratios was prepared into a nanoarray structure by chemical vapor deposition (CVD). The reactant was ammonium tetrathiomolybdate ((NH4)2MoS4), which was heated at 600 °C under an argon atmosphere for 10 hours to form a uniform MoS2 nanoarray.
[0055] Catalyst introduction
[0056] The obtained MoS2 nanoarray was immersed in a high-entropy metal salt solution composed of nickel chloride (NiCl2), iron chloride (FeCl3), cobalt chloride (CoCl2), zinc chloride (ZnCl2), and copper chloride (CuCl2) for 3 hours.
[0057] Structural synthesis
[0058] The immersed samples were subjected to instantaneous high-temperature Joule heat treatment at 1000℃ for 1 minute. This process generated NiFeCoZnCu high-entropy alloy nanoparticles and introduced sulfur vacancies into the MoS2 nanoarray, thereby forming a metal-semiconductor composite structure.
[0059] Performance testing
[0060] The photocatalytic performance of the samples was tested, and the results showed that the composite material exhibited excellent photocurrent response and photo-thermal-electric synergistic conversion efficiency at low temperatures. Further electrochemical tests showed that the introduction of sulfur vacancies significantly improved the low-temperature reversible charge transport performance of the material.
[0061] The following tests were conducted on the low-temperature photocatalytic and battery performance of the material:
[0062] Test conditions
[0063] The composite materials prepared in Examples 1 and 2 were applied to the cathode materials of light-driven solid-state batteries, and their performance was tested under low temperature (-20°C) conditions.
[0064] Test Results
[0065] The material in Example 1 exhibits strong absorption characteristics across a broad spectrum (300-1200 nm), with a photocurrent density reaching 5.2 mA / cm² at -20°C. 2 It is about 65% higher than that of materials without introduced oxygen vacancies.
[0066] The material in Example 2 exhibits higher photo-thermal-electric conversion efficiency at low temperatures, with a photocurrent density of 4.8 mA / cm². 2 Furthermore, electrochemical impedance spectroscopy (EIS) confirmed that its charge transport impedance was significantly reduced.
[0067] in conclusion
[0068] The above embodiments demonstrate that by introducing oxygen vacancies, sulfur vacancies, and high-entropy alloy nanoparticles, the photocatalytic and electrochemical performance of light-driven solid-state batteries under low-temperature conditions can be effectively improved.
[0069] In summary, this invention relates to a broadband, high-absorption, and highly efficient photo-thermal-electric conversion nanocomposite cathode photocatalyst material for light-driven solid-state batteries operating at low temperatures, including but not limited to multi-element alloy nanoparticles and one-dimensional semiconductor nanoarray composite structures rich in vacancies / defects. The multi-element alloy nanoparticles include, but are not limited to, binary alloy particles (RuAu, etc.) with sizes in the sub-nanometer and nanoscale range, and high-entropy alloy particles with ternary or higher dimensions. The one-dimensional semiconductor nanoarray structures rich in vacancies / defects include, but are not limited to, oxide semiconductor nanoarray structures rich in oxygen vacancies / defects (such as Ti5O9, etc.) and sulfide semiconductor nanoarray structures rich in sulfur vacancies / defects. Figure 2The multi-element alloy nanoparticles are assembled on a vacancy / defect-rich semiconductor nanoarray structure through strong interactions, forming a metal-semiconductor nanocomposite cathode catalyst structure with broad-spectrum strong absorption and efficient photo-thermal-electric synergistic conversion. The preparation method of the metal-semiconductor nanocomposite cathode catalyst structure of this invention uses Joule heating and other methods to perform instantaneous high-temperature heat treatment on oxide / sulfide semiconductor materials with standard stoichiometric ratios prepared by traditional physicochemical methods after immersion in a multi-element metal salt solution, thereby realizing the multi-element alloy nanoparticles, the vacancy / defect-rich semiconductor nanoarray structure, and the strong interactions between them. Figure 3 The metal-semiconductor composite structure designed in this invention couples the photocatalytic properties of low-dimensional semiconductor nanoarray structures with the plasmon effect of multi-element alloy nanoparticles, achieving broad-spectrum strong absorption of sunlight. Figure 5 While achieving efficient synergistic conversion of light-heat-electric energy, solid-state batteries can further enhance reversible charge transport and storage at low temperatures by introducing catalytically active sites such as "oxygen / sulfur vacancies" and "defects" on the material surface.
[0070] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode photocatalyst material for solid-state batteries, characterized in that, The positive photocatalytic material includes: A one-dimensional semiconductor nanoarray composite structure containing vacancies / defects, wherein the one-dimensional semiconductor nanoarray composite structure includes an oxide semiconductor nanoarray structure containing oxygen vacancies / defects or a sulfide semiconductor nanoarray structure containing sulfur vacancies / defects. Multi-element alloy nanoparticles, wherein the multi-element alloy nanoparticles are binary alloy particles and / or ternary or higher entropy alloy particles with sizes in the sub-nanometer and nanoscale range. The multi-element alloy nanoparticles are disposed on the one-dimensional semiconductor nanoarray composite structure.
2. The positive electrode photocatalyst material according to claim 1, characterized in that, The oxide semiconductor nanoarray structure containing oxygen vacancies / defects is selected from one of the following structures: Ti5O9 nanoarray structure, TiO2 nanoarray containing oxygen vacancies, or TiO2 nanoarray with additional oxygen vacancies introduced by doping with manganese (Mn) or chromium (Cr). x Nanoarrays.
3. The positive photocatalytic material according to claim 1, characterized in that, The sulfur-containing vacancy / defect sulfide semiconductor nanoarray structure is selected from one of the following structures: MoS2 nanoarrays containing sulfur vacancies, and WS2 nanoarrays generated under transition metal doping conditions; ZnS nanoarrays were prepared by chemical vapor deposition under high-temperature sulfidation conditions.
4. The positive electrode photocatalyst material according to claim 1, characterized in that, The multi-element alloy nanoparticles are selected from binary alloys and high-entropy alloy particles with ternary or higher elements formed from Ru, Ir, Co, Ni, Fe, Cu, Zn, and Mo metals.
5. A method for preparing a positive photocatalyst material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: 1) Prepare nanoarray structures from oxide or sulfide semiconductor materials with standard stoichiometry using physicochemical methods; 2) The obtained nanoarray structure was immersed in a multi-metal salt solution; 3) The soaked material is subjected to instantaneous high-temperature heat treatment using the Joule heating method to form a composite structure of multi-element alloy nanoparticles and one-dimensional semiconductor nanoarrays containing vacancies / defects.
6. The preparation method according to claim 5, characterized in that, In step 1), the oxide or sulfide semiconductor material with a standard stoichiometric ratio is TiO2, and the physicochemical method is the hydrothermal method.
7. The preparation method according to claim 5, characterized in that, In step 2), the multi-metal salt solution is either gold chloride solution or ruthenium chloride solution.
8. The preparation method according to claim 5, characterized in that, In step 3), the Joule heating method is an instantaneous high-temperature heat treatment method with a temperature range of 500°C to 1200°C and a treatment time of several seconds to several minutes.
9. A positive electrode for a battery, characterized in that, It includes the positive electrode photocatalytic material as described in any one of claims 1-4 or the positive electrode photocatalytic material prepared by the preparation method as described in any one of claims 5-8.
10. A solid-state battery, characterized in that, Includes the battery positive electrode as described in claim 9.
Citation Information
Cited By
A photocatalyst for TiO2 nanoflower-supported CoNiCuPdAg high-entropy alloy, its preparation method, and its application.
CN122399920A